Atenolol Reduces Leishmania major-Induced Hyperalgesia and TNF-α Without Affecting IL-1β or Keratinocyte Derived Chemokines (KC) - Karam, Marc C.; Merckbawi, Rana; Salman, Sara; Mobasheri, Ali (Frontiers in Pharmacology, 2016)
Infection with a high dose of the intracellular parasitic protozoan L. major induces a sustained hyperalgesia in susceptible BALB/c mice accompanied by up-regulation of the pro-inflammatory cytokines IL-1β and IL-6. Interleukin-13 (IL-13) has been shown to reduce this hyperalgesia (despite increased levels of IL-6) and the levels of IL-1β during and after the treatment period. These findings favor the cytokine cascade leading to the production of sympathetic amines (involving TNF-α and KC) over prostaglandins (involving IL-1β and IL-6) as the final mediators of hyperalgesia. The aim of this study was to investigate the effect of daily treatment with the β-blockers atenolol on L. major-induced inflammation in mice with respect to hyperalgesia as well as the levels of TNF-α and KC (the analogue of IL-8 in mice). Our data demonstrates that atenolol is able to reduce the L. major induced sustained peripheral hyperalgesia, which does not seem to involve a direct role for neither IL-1β nor KC. Moreover, our results show that TNF-α may play a pivotal and direct role in sensitizing the peripheral nerve endings (nociceptors) since its level was reduced during the period of atenolol treatment, which correlates well with the reduction of the observed peripheral, but not central, hyperalgesia. These findings contribute to a better understanding of the cytokine cascade leading to hyperalgesia and may lead to the development of new and more efficient medications for many types of pain.